2020
DOI: 10.3390/app10217395
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hybrid Wind-Wave Energy Resource for the NW Coast of Iberian Peninsula in a Climate Change Context

Abstract: Offshore renewable energy has a high potential for ensuring the successful implementation of the European decarbonization agenda planned for the near future. Hybrid wind-wave farms can reduce installation and maintenance costs, and increase the renewable energy availability of a location by compensating for the wind’s intermittent nature with good wave conditions. In addition, wave farms can provide protection to wind farms, and the combined wind/wave farm can provide coastal protection. This work aims to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Finally, it should be highlighted that although the technology for the wave energy extraction is not yet fully effective, the very high dynamics as regards the offshore wind is expected to induce momentum to the wave energy industry as well [69,70]. From this perspective, a first step would be to collocate wave farms in the vicinity of the already operating wind farms; in this way, both the capital and operational costs would be substantially decreased [71,72]. Furthermore, another expected advantage of the future wave energy farms is that by absorbing the incoming wave energy in the nearshore, they can also provide coastal protection [73,74], bringing a beneficial role in the balance of the nearshore processes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be highlighted that although the technology for the wave energy extraction is not yet fully effective, the very high dynamics as regards the offshore wind is expected to induce momentum to the wave energy industry as well [69,70]. From this perspective, a first step would be to collocate wave farms in the vicinity of the already operating wind farms; in this way, both the capital and operational costs would be substantially decreased [71,72]. Furthermore, another expected advantage of the future wave energy farms is that by absorbing the incoming wave energy in the nearshore, they can also provide coastal protection [73,74], bringing a beneficial role in the balance of the nearshore processes.…”
Section: Discussionmentioning
confidence: 99%
“…The RMSE and Bias indicators show that the BCC-CSM1.1 GCM represents the best climate model to reproduce the IP west coast's extreme wave climate. These results show that model performance can be seasonal specific as [50,51] found that MIROC5 GCM was the best model to reproduce the area's annual mean wave conditions.…”
Section: Wave Statistical Analysismentioning
confidence: 75%
“…The skill of these CMIP5 GCMs was evaluated in previous studies [50,51] for the Northwest IP coast. This performance metric of GCMs has been applied [52][53][54][55][56][57] to explore the frequency and severity of climate extremes and has been useful to evaluate the climate models.…”
Section: Wave Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of this multimodel ensemble to reproduce wind speed at 10 m asl in the study area was previously demonstrated by comparing numerical wind speed series with in situ data from buoys using different statistical metrics (percentage of error, overlap percentage, root-mean-square error, and percentage of difference in median wind speed series) [ 18 , 24 , 34 ]. In particular, according to F. Santos et al (2018), the percentage of error between the mean wind projected for each RCM and the mean wind at each buoy is around 10% for the whole Iberian Peninsula and around 8% for the buoys located in the area under study.…”
Section: Methodsmentioning
confidence: 99%